Strategi pembelajaran Pendidikan Kewarganegaraan untuk memperkuat literasi digital mahasiswa - Nur Cholifah; Nila Sari; Ade Ricky Rozzaqi; Siswanto Siswanto (Journal of Education, Cultural and Politics, 2026)
The increasingly intensive use of social media among university students has reshaped the ways they obtain information, engage in discussion, and form views within the public sphere. This development has positioned digital literacy as an important concern for higher education institutions. Previous studies have largely described students’ levels of digital competence through surveys, while limited attention has been given to how such capacities are developed through learning experiences, particularly within the context of Civic Education. This study aims to examine learning strategies in Civic Education for strengthening students’ digital literacy. A qualitative approach with a case study design was employed at a private university in Semarang. The study involved two lecturers and ten students over one academic semester. Data were collected through observation, in-depth interviews, and document analysis, and were analysed thematically through repeated coding and interpretation. The findings indicate that students became more engaged when course materials were connected to issues closely related to their everyday digital experiences. Discussions concerning misinformation, data privacy, and online ethics made classroom interaction more dynamic and encouraged the habit of verifying information sources before using them as references. Within the same process, students became more careful in expressing their views and more open to differing perspectives. These findings suggest that Civic Education should not be confined to the transmission of normative values, but can extend its function as a pedagogical space for fostering critical, ethical, and responsible digital citizenship. Accordingly, curriculum development needs to provide clearer space for information verification, digital ethics, and healthy public participation.